Distorsiones de productividad en el sector formal en Colombia (2020)
This research provides empirical evidence that allows knowing the distribution and allocation of firms productivity that operate in the formal sector in Colombia. With the purpose of contributing to the understanding of the distribution and allocation of productivity in all sectors including non-manufacturing. For its development, unlike the studies that have been carried out to date in Colombia and that are frequently a source of information for the development of these analyzes, censuses or surveys, this research takes advantage of the information recorded in administrative records, to study the distortions in the allocation of resources in the Colombian case, and thus know how serious are the distortions of productivity of companies in Colombia and what factors are associated with the misallocation of resources? To study the role of misallocation in Colombia, the methodology proposed by Hsieh-Klenow (2009)...